2015
DOI: 10.1186/s12876-015-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative MRCP necessary for patients with gallstones? An analysis of the factors related to missed diagnosis of choledocholithiasis by preoperative ultrasound

Abstract: BackgroundThe diagnosis of associated choledocholithiasis prior to cholecystectomy for patients with gallstones is important for the surgical decision and treatment efficacy. However, whether ultrasound is sufficient for preoperative diagnosis of choledocholithiasis remains controversial, with different opinions on whether routine magnetic resonance cholangiopancreatography (MRCP) is needed to detect the possible presence of common bile duct (CBD) stones.MethodsIn this study, a total of 413 patients with galls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
1
21
0
2
Order By: Relevance
“…We analyzed patients with preoperative suspicion of choledocholithiasis rather than all patients undergoing cholecystectomy, as our aim was to test the clinical utility of guidelines in preoperative suspected choledocholithiasis. This might have changed diagnostic accuracy only slightly, as two previous studies have shown that CBD stone with normal LFT is rare and accounts for only 1.69 % -5.4 % of all cases [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed patients with preoperative suspicion of choledocholithiasis rather than all patients undergoing cholecystectomy, as our aim was to test the clinical utility of guidelines in preoperative suspected choledocholithiasis. This might have changed diagnostic accuracy only slightly, as two previous studies have shown that CBD stone with normal LFT is rare and accounts for only 1.69 % -5.4 % of all cases [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of having CBDSs in spite of normal LFTs and ultrasonography has been adequately evaluated in two studies [35,36]. In a large study including 765 patients with ERCPproven CBDSs, 541 had previously documented LFTs and 29 (5.4 %) had normal LFTs.…”
Section: Initial Evaluationmentioning
confidence: 99%
“…Age more than 55 years and the presence of pain were independently associated with normal LFTs in patients with CBDSs [35]. A more recent retrospective study including 413 patients with gallstones who underwent ultrasonography and magnetic resonance cholangiopancreatography (MRCP) for suspected CBDSs showed that 109 /413 (26.3 %) had CBDSs revealed on the MRCP, but in 7 /109 (6.4 %) ultrasonography and LFTs (one or more of total bilirubin, ALP, AST, ALT, or GGT) were normal [36] (Table 2 s).…”
Section: Initial Evaluationmentioning
confidence: 99%
“…The tested population did not reflect known malignancy, chronic pain, or painless jaundice. The prevalence of choledocholithiasis in the overall population for the base case was 27% (accounting for all manifestations of symptomatic gallstone disease, including cholecystitis and pancreatitis) (45,(53)(54)(55). In the base case of patients with known gallstones at presentation, 10% of patients had a biliary stricture, and 10% of strictures had a malignant etiology of obstruction (resulting in 1% risk of malignancy overall); these probabilities were varied in sensitivity analysis (39,40,56).…”
Section: Model Population and Treatment Of Diseasementioning
confidence: 99%